Chapter The (not so violent) staseis and metabolai in the Aristotelian Athenaion Politeia - Correa, Denis (Studi e saggi, 2022)
The Athenaion Politeia chapter 41.2 lists eleven changes (metabolai) to the Athenian political system from the heroic age to the democratic restoration of Thrasybulus in 403 BCE; the city allegedly remained unchanged until as late as the writing of the text, probably around the 330s BCE. This text examines some patterns in the metabolai, involving the innovations ascribed to the first three (or four) and the main role played by Solon after the dissension (stasis) in which he acted as an arbitrator and avoided the establishment of a tyranny, which, according to the work, marked the beginning of democracy. After Solon, each subsequent metabole implicated his legacy, except those that involved tyranny. This pattern oversimplifies complex historical events, but the relationship between staseis and metabolai structures the Athenaion Politeia's original design and constitutional historical approach. While some of these changes (the fourth, fifth, tenth, and eleventh) entailed the violent seizure of power by or against tyrants, others relate to the Solonian ideal of managing staseis without the violence of tyranny, that is, by increasing (or limiting) the power of the people over the constitution.